Development of a numerical multi-layer model of skin subjected to pulsed laser irradiation to optimise thermal stimulation in photorejuvenation procedure. (April 2022) - Muddassir, Muhammad; Limbert, Georges; Navarro-Alarcon, David
Highlights: Time-dependent photo-thermal biophyics-based model of laser-skin interactions to simulate laser-based skin photorejuvenation procedures. The model accounts for the thermal and optical properties of individual skin layers (epidermis, dermis, hypodermis). Direct sensitivity analysis of the photo-thermal model with respect to its biophysical parameters demonstrating the high-sensitivity of thermal effects to skin melanin content. Important implications for treatment procedures in ethnically-diverse populations. Depth-controlled thermal stimulation of skin across its layers. The model offers a promising simulation platform to optimise laser-based photorejuvenation procedures. Abstract: Background and Objective: This paper presents the development of a 3D physics-based numerical model of skin capable of representing the laser-skin photo-thermal interactions occurring in skin photorejuvenation treatment procedures. The aim of this model was to provide a rational and quantitative basis to control and predict temperature distribution within the layered structure of skin. Ultimately, this mathematical and numerical modelling platform will guide the design of an automatic robotic controller to precisely regulate skin temperature at desired depths and for specific durations. Methods: The Pennes bioheat equation was used to account for heat transfer in a 3D multi-layer model of skin. The effects of blood perfusion, skin pigmentation and various convection conditions are also incorporated in the proposed model. The photo-thermal effect due to pulsed laser light on skin is computed using light diffusion theory. The physics-based constitutive model was numerically implemented using a combination of finite volume and finite difference techniques. Direct sensitivity routines were also implemented to assess the influence of constitutive parameters on temperature. A stability analysis of the numerical model was conducted. Results: Finally, the numerical model was exploited to assess its ability to predict temperature distribution and thermal damage via a multi-parametric study which accounted for a wide array of biophysical parameters such as light coefficients of absorption for individual skin layers and melanin levels (correlated with ethnicity). It was shown how critical is the link between melanin content, laser light characteristics and potential thermal damage to skin. Conclusions: The developed photo-thermal model of skin-laser interactions paves the way for the design of an automated simulation-driven photorejuvenation robot, thus alleviating the need for inconsistent and error-prone human operators.